Le Quah Langkawi Restaurant / Syazwan Firdaus Humala Darwis... [et al.] - Humala Darwis, Syazwan Firdaus; Ahmad, Mohd Fudlullah; Mat Noh, Mohad Faiz; Munir, Mohd Saiful Bari; Isyak, Shamsul Shaharil (2000)
Le Quah Restaurant is a foods and drink restaurant stated in Pekan Kuah, Langkawi Kedah. They served western, local and desserts in their restaurant. they started their business on 13 January 2003. this company is a partnership company.